1993
DOI: 10.1007/bf01956737
|View full text |Cite
|
Sign up to set email alerts
|

The long-term effect of cyproterone acetate on growth in girls with idiopathic precocious puberty

Abstract: To define the effect of cyproterone acetate (CPA) on statural growth, 25 girls with idiopathic precocious puberty who had been treated with CPA were studied retrospectively. The final height SDS was -1.12 +/- 1.16 (mean +/- SD). The daily CPA dose was negatively related to the final height SDS. We divided our subjects into two groups according to the daily CPA dose [low dose, 84.9 +/- 15.4 mg/m2 (n = 19) vs high dose, 135.8 +/- 17.1 mg/m2 (n = 6)]. In the low dose group, the difference of the final height SDS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In contradistinction, CyA suppresses gonadotrophin secretion incompletely [33], and has some undesirable side effects [34,35], Treatment with CyA may also become irregular and inconsistent with time, as noted with any chronic oral therapy in chil dren. This may be an additional reason for the less favor able FHt outcome reported for CyA treatment in CPP [36][37][38]. In this study we included only patients for whom regular and consistent treatment with CyA was registered and its long-term effect on FHt proved to be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…In contradistinction, CyA suppresses gonadotrophin secretion incompletely [33], and has some undesirable side effects [34,35], Treatment with CyA may also become irregular and inconsistent with time, as noted with any chronic oral therapy in chil dren. This may be an additional reason for the less favor able FHt outcome reported for CyA treatment in CPP [36][37][38]. In this study we included only patients for whom regular and consistent treatment with CyA was registered and its long-term effect on FHt proved to be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…CPA is used in adults for treatment of prostate and breast cancer, uncontrolled sexual urges, hirsutism and acne. In children, before the introduction of gonadotropin-releasing-hormone (GnRH) analogues, CPA was the most frequently used drug for the treatment of precocious puberty [7,16,13,22]. Moreover, it is still prescribed by some as temporary concomitant treatment to GnRH analogues, to counteract its possible initial stimulatory eect, before gonadotropin secretion ensues [15].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the change in height SDS Table 5 Correlation coefficients for predicted final height (PFH) at the final estimation and various variables in the older group for bone age was greater in the younger group also shows the importance of the effect of growth velocity on final height. Kato et al (4) report that the final height of girls with central precocious puberty was greater in patients who received low-dose cyproterone acetate (CPA) than in patients who received high-dose CPA and speculate that high-dose CPA might cause a greater growth velocity reduction than a suppressive effect on bone age maturation. Our study's findings agree with those of Kato et al The average growth velocity showed a significant negative correlation with the average dose: the higher the dose, the lower the growth velocity.…”
Section: Discussionmentioning
confidence: 99%
“…ported that gonadal suppressive agents such as cyproterone acetate and LHRH analog can effectively regress or arrest pubertal development, but the results of the effect on improvement of final height are still controversial (1)(2)(3)(4)(5)(6)(7). Final height is thought to be influenced by the rate of deceleration of bone age maturation and growth rate during treatment.…”
mentioning
confidence: 99%